GAMBARAN NILAI SATURASI OKSIGEN (SO2) DENGAN TEKANAN OKSIGEN (PO2) PADA PASIEN PENYAKIT JANTUNG KORONER (PJK) DI RUMAH SAKIT UMUM DAERAH JAYAPURA - Paulina Kadam; Ni Putu Rahayu Artini; I Wayan Tanjung Aryasa (Universitas Muhammadiyah Surabaya, 2020)
Coronary heart disease (CHD) patients are equipped with blood tests to reinforce the diagnosis of the patient's disease. One of the parameters that is usually checked is blood gas analysis (AGD). One of the parameters of blood gas analysis (BGA) is oxygen saturation (SO2), oxygen pressure (PO2), and carbon dioxide pressure (PCO2). The purpose of this study was to determine the relationship between SO2, and PO2,at the Jayapura Regional General Hospital. This type of research is retrospective analytic. The sample of this study were coronary heart patients who underwent BGA xamination at the Jayapura General Hospital who met the inclusion criteria, so that 30 samples were obtained. The type of data is secondary data. With the mean value of SO2 is 96,1% and PO2 is 133,2 mmHg. The results of the relationship between SO2 and PO2 in coronary heart disease patients at Jayapura Regional Hospital are directly proportional, namely the decrease in SO2, PO2 will also decrease in CHD patients, with four people experiencing moderate hypoxemia, five people with normal PO2, and 21 people with PO2 is high because you have got a ventilator device.